Developing SOI (Suggestion, Offer and Invitation) as Instructional Media in Writing Skill for XI Grade of MA’ Maarif 1 Jombang - Afidah, Nurul; Anandita, Septian Ragil; Amna, Rosma Zakiyah (Universitas KH. A. Wahab Hasbullah, 2023)
In this global era, many people use English as a media of communication and make it people who come from different countries to be easier in interacting and communicating. As the one of international language in the world English in education that covers four language skills: listening, speaking, reading and writing. Writing is skill is one of language skill that is important so that it must be mastered by English learners. The purpose of this research is to develop product SOI as instructional media in writing skill for XI grade. This research was conducted at MA’ Maarif 1 Jombang in XI grade. There are nine students who participated in this research. The method used in this study is research and development by adapting ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Based on the validation result of the experts by getting score of 88% and 83% that was good respectively with feasible and usable and the result of data analysis got score 85% respectively which proper criteria